IL-13 Derived Type 2 Innate Lymphocytes Ameliorates Cardiomyocyte Apoptosis Through STAT3 Signaling Pathway - Hong, Ting; Li, Saiqi; Guo, Xiaoyu; Wei, Yazhong; Zhang, Jingjing; Su, Xiaohui; Zhou, Miao; Jin, Haizhen; Miao, Qing; Shen, Lei; Zhu, Minfang; He, Bin (Frontiers in Cell and Developmental Biology, 2021)
The involvement of cardiomyopathy during sepsis means higher mortality and prolonged length of hospital stay. Many efforts have been made to alleviate the apoptosis of cardiomyocytes in sepsis. The huge potential of IL-13 in tissue repair has attracted increasing attention. In the present study, we used LPS-treated mice or primary cardiomyocytes as a sepsis model to explore the anti-apoptotic ability of IL-13. It was found that an increased level of exogenous IL-13 was beneficial to the recovery of heart function in sepsis, and this anti-apoptotic effect of IL-13 was probably through enhancing the phosphorylation of STAT3 Ser727. In addition, we identified that the heart protective effect of IL-13 was associated with type 2 innate lymphocytes (ILC2). All these findings may provide a potential promising treatment for sepsis-induced cardiomyopathy.